Comorbidity of Obsessive-Compulsive Disorder and Schizotypal Personality Disorder: Clinical Response and Treatment Resistance to Pharmacotherapy in a 3-Year Follow-Up Naturalistic Study - Perris, Francesco; Fabrazzo, Michele; De Santis, Valeria; Luciano, Mario; Sampogna, Gaia; Fiorillo, Andrea; Catapano, Francesco (Frontiers in Psychiatry, 2019)
The present study aims to analyze the clinical and socio-demographic characteristics of patients with obsessive-compulsive disorder in comorbidity with schizotypal personality disorder, as well as their response to pharmacological treatment. Compared to patients without schizotypal personality disorder, those affected by both disorders in comorbidity had a younger age at onset, a higher probability to have more severe obsessive-compulsive symptoms, a higher rate of schizophrenia spectrum disorders in their first-degree relatives, and a poorer insight. During the 3-year follow-up, these patients showed a lower likelihood to recover, thus requiring augmentation with different psychotropic medications, including low doses of antipsychotics. Our findings suggest that the comorbidity of obsessive compulsive disorder and schizotypal personality disorder causes a poor treatment response in OCD patients, and a reduced probability to recover, under standard pharmacological treatment strategies. Further investigations are needed to identify alternative strategies, including psychoeducation and CBT, to manage this frequent comorbidity in clinical practice.